Romanticism and Colonial Ideology in Thomas Stamford Raffles’s Production of the Hikayat Damar Bulan Manuscript - Windayanto, Riqko Nur Ardi (Malay Literature, 2025)
This study aims to uncover the romantic-colonial ideology of Sir Thomas Stamford Raffles, who acted as a patron in the production of the Hikayat Damar Bulan manuscript (RAS 11). Employing narrative analysis, the study examines the portrayal of Damarwulan in the text, followed by a discursive analysis within a codicological framework (including the manuscript’s date, origin, scribe, and patron) and considers the historical context of British colonialism in Java. The findings reveal that the Hikayat Damar Bulan was completed in 1815 under the direction of Raffles. The manuscript was copied from the Serat Damarwulan and the wayang krucil performances, which were popular along the northern coast of Central Java. In the tale, Damarwulan is depicted as a hero who maintains and protects the integrity of Majapahit from the threat of Menak Jingga, a narrative positioning symbolising the ideal order. This position suggests that the manuscript contains a romanticised portrayal of an ideal order rooted in the Hindu-Buddhist era of Majapahit, rather than the Islamic forces of 19th-century Java, which Raffles perceived as sources of disorder and threats to colonial rule. The manuscript serves as material evidence of Raffles’ romanticism—his desire for a harmonious order in which colonial power could be institutionalised and exercised without resistance. Thus, this study concludes that Hikayat Damar Bulan is a romantic manuscript, produced with and for the purpose of articulating Raffles’ romantic ideology, an ideology that was discursively shaped within the context of colonialism and among 19th-century colonial scholars. Full text:   PDF